On-earth performance evaluation of SatCom on-the-move (SOTM) terminals - Alazab, Mostafa; Rieche, Marie; Del Galdo, Giovanni; Felber, Wolfgang; Raschke, Florian; Siegert, Gregor; Landmann, Markus (Proceedings - IEEE Military Communications Conference MILCOM, 2013)
Applications for SatCom On-The-Move (SOTM)are intended to provide mobile users with communication services such as internet at all the times and places. However, fading due to objects surrounding the earth terminal and antenna depointing due to the vehicle motion represent the main challenges for the development of SOTM systems. Both lead to degradation in the overall Quality of Service (QoS). Moreover, antenna depointing may lead to harmful interference to adjacent satellites. Regulatory authorities define limits for antenna de-pointing and for the Power Spectral Density (PSD) transmitted from the antenna. An integral part of the development of SOTM systems is to demonstrate their overall performance as well as to test the performance of the tracking unit. Such tests and demonstrations are usually performed in field tests where two operational satellites are involved. This contribution proposes an alternative test method which avoids the employment of operational satellites and offers a reliable and repeatable environment for measuring the overall SOTM system performance. Antenna pointing errors can be estimated with higher accuracy along azimuth and additionally along elevation. The proposed method employs a cross shaped sensor array for antenna de-pointing estimation. We therefore name it the 'Sensor-Array' method. This contribution compares the performance of this method w.r.t. the state-of-theart, confirming its advantages. © 2013 IEEE.
CRIS-Team Scopus Importer:2025-11-10